The impact of microfinance on the growth of micro, small and medium enterprises in Namibia - Uusiku, Elise Peneyambeko (Graduate School of Business (GSB), 2019)
Many governments around the world have recognised the vital role that Micro, Small and Medium Enterprises (MSMEs) play in promoting economic growth and restoring economies. Though with much recognition, MSMEs financing remains a challenge. Microfinance is regarded as a prominent tool in addressing the financing gap that emanates within the SMEs sector. Yet, the extent to which such initiative has prospered in addressing the funding gap is understudied. Therefore, this paper explored the impact of microfinance services on the growth of Micro, Small and Medium Enterprises (MSMEs) in Namibia. The study employed a cross-sectional analysis on 45 small enterprises to examine the effect of microfinance activities on the productivity of MSMEs in Oshana region. The sample was drawn from a list of MSMEs who have accessed microfinance services offered by the Development Bank of Namibia. It uses the multiples regression to test the influence of a group of variables (types of microfinance, gender, business location, education, years of existence and the amount of loan received) on productivity a proxy for business growth. The research indicated that a combination of loan (microcredit) and training as well as the number of years that the business has been in existence had a significant impact of productivity (proxy for growth). Consequently, microcredit as a main variable did not significantly contribute to MSMEs growth. Therefore, the study argues that gaining access to microcredit alone cannot lead to small business growth but rather a combination of other important variable such as education and business experience are essential for the full utilization of microcredit which may result in the growth of MSMEs. Likewise, poor management skills hindered the MSME’s ability to fully utilise microfinance services. The study further recommended that Microfinance Institutions should consider other factors such as advisory services, training and mentorship services. Therefore, a designed packages that combined different services other than the stand-alone package for microcredit is ideal to ensure that loans disbursed are fully utilized and maximised.